Book Reviews (Res Medica, 2013)
INTRA-ABDOMINAL CRISES by K. D. Keele, M.D., F.R.C.P., and N. M. Matheson, F.R.C.S., M.R.C.P., F.A.C.S. Pp. 397. Published by Butterworths. Price 50s. plus 2s. by post.It has become increasingly obvious that the ancient distinction between physician and barber surgeon is an unreal one; and nowhere is this more obvious than in the field of abdominal disorders. Edinburgh has recognised the need for close collaboration between physicians and surgeons in the shape of the gastro-intestinal unit at the Western General Hospital. DILLING'S CLINICAL PHARMACOLOGY. revised by Stanley Alstead. C.B.E., M.D., F.R.F.P.S., F.R.C.P. Lond., F.R.C.P.Edin., F.R.S.Edin. and others. 20th Edition, Pp. 860. Published by Cassel & Company Ltd. Price 30s. net.This textbook is notable for the wide limits of the topics discussed under the heading of pharmacology. The authors have succeeded in gathering together under each chapter heading the physiological principles involved in the working of each system and have attempted to relate the pharmacology of the drugs under discussion to them. They go on to carefully and logically show the rationale of the use of the drugs in medicine. At the same time, wherever possible, they demonstrate that the same pharmacological actions are also responsible for the toxic actions and side effects. In this way it is possible to assess the benefit of a drug to the patient against a background of knowledge which also allows the risks involved to be estimated.